The Integrating Mini PLC FX1N with Raspberry Pi for Prototyping of Industrial Control - Kirasamutranon, Lerchai; Akkarathanakul, Pathitta; Pongphoo, Thanakorn; Surachotivet, Sirawat; Poungsri, Piyapat; Thaenkaew, Pakamas; Saengsawang, Weerapong; Charoensuk, Kritchanan; Pawananont, Kanchit (2025 13th International Electrical Engineering Congress (iEECON), 2025)
In contemporary industries, machine languages have become essential for producing various products and services. Ladder Logic is a prominent programming language commonly utilized in different sectors, including web development, software engineering, data science, and machine learning. Conversely, C and C++ are versatile programming languages that support object-oriented and procedural programming paradigms and effective memory management. These languages find applications in diverse fields, such as embedded systems and ladder programming, where ladder logic diagrams represent machinery control systems. Programmers must possess a comprehensive understanding of system operations and effectively use a variety of symbols to indicate specific functions to create a ladder diagram accurately. Tasks involving Programmable Logic Controllers (PLCs) typically require computer and communication software, such as the Raspberry Pi Pico microcontroller board. GX Works2 is a PLC software application that facilitates the testing and simulation of different three-phase motor circuits, thereby enabling precise control of actual power equipment. This article describes programming hardware control systems with Ladder language. This language is crucial for coding Programmable Logic Controllers (PLCs), widely used in industrial plants.